Évora Studies in the Philosophy and History of Science In Memoriam Hermínio Martins, prefácio e edição de João Príncipe - Príncipe, João (2016)
Since 2010, Hermínio Martins was a regular participant in the Évora International Symposia in the Philosophy and History of Science. On the occasion of the sixth of these symposia, the first one to take place after he passed away, his invaluable contribution is here celebrated through the publication of his collected works in philosophy of science. This important set of texts, written and rewritten during forty years, is accompanied by contributions from other participants in the earlier symposia.